FloodPlans landscape plan for a flood resilient Municipality of Marilao, Bulacan - Aquino, Gizelle Lindsay V.; Honorio T. Palarca (Quezon City : College of Architecture, University of the Philippines Diliman, 2020)
According to the Philippine Atmospheric, Geophysical and Astronomical Services Administration (PAGASA) the Philippines is visited by an average of 20 typhoons a year; and one of the main repercussions of typhoons is flooding. Due to worsening and intensifying typhoons (Mei, 2016), the problem on flooding is also getting worse, and one of the main reasons for this is: land subsidence and sea level rise. Marilao, Bulacan, is one of the municipalities that is experiencing worsening flood levels (Rodolfo et al., 2003). An environmental approach on making the municipality adaptive and resilient to flooding was used in order to find the most appropriate use of the land areas of Marilao – to both benefit the environment and its users. In order to draft an effective plan for the municipality, the study identified and analyzed the causes of flooding, with the aid of relevant maps such as hazard maps, existing land use plan, and projected land use plans. After which, projections of the land conditions on the next century were generated in order to ensure that the propose plans will accommodate future scenarios within the landscape. These data, along with four possible scenarios on the problems of the site were analyzed. With this, the study took upon one of the approaches which led to the 2060 Environmental Protection Plan which has its primary focus of addressing landscape requirements.
Thesis (Bachelor of Landscape Architecture) -- University of the Philippines Diliman
Keywords: City planning -- Environmental aspects; Flood control -- Marilao (Bulacan); Flood damage prevention -- Marilao (Bulacan); Floods -- Marilao (Bulacan)